The Application and Assessment of the Importance of the Most Frequently Used Intelligent Logistics Systems in Manufacturing Enterprises in Poland - Part One - Robert STANISLAWSKI (Communications of International Proceedings, 2021)
Intelligent systems in production and logistics (ISL) are increasingly used. Due to this fact, this topic becomes more and more the subject of research, both from the practical and theoretical point of view. On the one hand, the importance of ISL is the results of the advantages such as: greater production flexibility and easier adaptation to customer requirements, faster deliveries, or increased efficiency and effectiveness of decision-making processes undertaken in enterprises, on the other hand, from the necessity of changes forced by the environment. In the range of this article, an analysis of the three most frequently used systems was carried out, i.e. the Internet of Things, Data Base and cloud computing. It was based on our own research which concerned many important issues: determining the universality and purpose of using ISL in manufacturing companies at various stages of the logistics process, cooperation with various IT systems or indicating the main advantages and disadvantages of using ISL. The research was conducted in 2020 on a sample of over 100 companies using logistic chains in their activities. The purpose of this article is to identify the use and importance of ISL among the studied entities. This goal has been narrowed down only to those systems that are the most "popular" – it means - the most famous among Polish enterprises. The analysis of less known systems is presented in the next article - the second part written by another author. Both these articles are complementary to each other and constitute a whole that serves the presentation of the discussed phenomenon (realization of the assumed goal).
Keywords: Intelligent Systems In Production And Logistics; Production Companies; Internet Of Things; Big Data; Cloud Computing